Kolaborasi E-Learning Manajemen Keperawatan terhadap Peningkatan Kompetensi Mahasiswa Keperawatan - Yusnaini Yusnaini; Prodalima Prodalima; Juliana Irawati (Jurnal Keperawatan Silampari, 2022)
This study aims to analyze the effect of e-learning collaboration in nursing management on improving the competence of nursing students at STIKes Nurul Hasanah Kutacane. This research design is quasi-experimental with pre and post-test without control. The results showed that the average competence of nursing students before the e-learning collaboration in nursing management was 129.51. The intermediate competency of nursing students after e-learning collaboration in nursing management is 158.97. In conclusion, there is a significant effect of e-learning collaboration on nursing management on increasing nursing student competence. Nursing management e-learning collaboration has a positive impact on improving student competence. Keywords: E-Learning, Collaboration, Competence